2019
DOI: 10.5398/tasj.2019.42.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Agricultural By-Products as Feed by Beef Cattle Farmers in Maros Regency of South Sulawesi, Indonesia

Abstract: The utilization of crop residue as a feed is very important because the arable land area is relatively limited. The study was aimed to examine the influence of adoption of crop-residue product as a feed. The research was conducted in Maros District by using survey methods from March to August 2015. The number of respondents was 96 farmers scattered throughout the Districts of Bantimurung and Camba as centers of rice, corn plant, and cattle productions. Questionnaires were used to collect data conducted by a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…It revealed that most farmers from both partial integration and full integration category used unprocessed manures as fertilizer (64.7%) and fresh paddy straw as cattle feed (76.6%). Some studies revealed that the main reason for farmers utilized manure as fertilizer was the ability of manure that could improve the soil fertility, while the main reason for farmers utilized straw as feed was farmers holding limited land fodder (Case et al, 2017;Baba et al, 2019). The present study showed that 59.1% of farmers cultivated elephant grass or king grass on the rice fields' edge, and 29.8% of farmers did not have land fodder.…”
Section: Farm Waste Management Technologymentioning
confidence: 51%
“…It revealed that most farmers from both partial integration and full integration category used unprocessed manures as fertilizer (64.7%) and fresh paddy straw as cattle feed (76.6%). Some studies revealed that the main reason for farmers utilized manure as fertilizer was the ability of manure that could improve the soil fertility, while the main reason for farmers utilized straw as feed was farmers holding limited land fodder (Case et al, 2017;Baba et al, 2019). The present study showed that 59.1% of farmers cultivated elephant grass or king grass on the rice fields' edge, and 29.8% of farmers did not have land fodder.…”
Section: Farm Waste Management Technologymentioning
confidence: 51%
“…On the other hand, extension service either from the DVS or among the farmer's association plays as the main actor to ensure the increase in cattle production and sustain in this sector. Their active role among farmer's community is essential to help them know about the current innovation and practice it at their farm (Baba et al, 2019;Paul et al, 2017). Some of the farmers were more comfortable with the farmer's association than the DVS extension worker.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies conducted by researcher on introducing the innovations in beef cattle farming, but unfortunately, those introduced innovations do not well assist by the extension workers, and farmers are financially unstable to invest in particular innovation (Baba, Dagong, & Risal, 2014;Baba et al, 2019;Wahyudi, 2017). Thus, this study aims to bridge the knowledge gap in the adoption of innovation among beef cattle farmers.…”
Section: Figure 1 Percentage Of Self-sufficiency Level For Livestock Productsmentioning
confidence: 98%
See 2 more Smart Citations